John’s use of Scripture in Revelation 1:7 - M. J.J Menken (In die Skriflig, 2007)
Four questions are asked in this paper: (1) Which are the Old Testament passages from which John quotes in Revelation 1:7? (2) To what extent do the separate quotations and their combination belong to the early Christian tradition used by John? (3) How and where did this combination of quotations come into being? (4) What does John aim at with this com- bination of quotations in this context? John makes use of the combination of God’s eschatological agent as depicted in Daniel 7 and the “pierced one” from Zechariah 12 into one figure, to present the traditional early Christian eschatology, phrased in Old Testament terms, as the basis and the starting point of his book.